THE EFFECT OF FINANCIAL CONSTRAINT MODERATION IN CASH FLOW SENSITIVITY TO EXTERNAL FINANCING OF MANUFACTURING COMPANIES - Abu Hasan Ahmad; Maria Adventia Mentari Mayang Cardicna (Universitas muhammadiyah malang, 2020)
This study aims to test the pecking order theory by looking at the level of cash flow sensitivity as a source of internal financing for all types of external financing (debt and equity). This testing also considering the financial constraint variable as moderation. The data used are the financial statements of manufacturing companies listed on the Indonesia Stock Exchange in 2014 - 2018. The dependent variable is all types of external financing (debt and equity). Debt financing is divided into two forms, short-term debt financing and long-term debt financing. While the independent variable is cash flow. The results obtained is that cash flow does not substitute all types of external financing, and the highest cash flow sensitivity occurs in short-term debt financing. The next result is that financial constraint strengthen the sensitivity of cash flow to debt and equity financing